Induced global deletion of glucocorticoid receptor impairs fracture healing. Issue 4 (5th January 2018) - Rapp, Anna E.; Hachemi, Yasmine; Kemmler, Julia; Koenen, Mascha; Tuckermann, Jan; Ignatius, Anita
Abstract : Although endogenous glucocorticoids (GCs) are important regulators of bone integrity and the immune system, their role in bone repair after fracture—a process highly dependent on inflammation and bone formation–is unclear. Because most effects of GCs are mediated by the glucocorticoid receptor (GR), we used an inducible global GR knockout (GR gtROSACreERT2 ) mouse model to eliminate endogenous GC action in all cells contributing to bone repair. The healing process was analyzed by cytokine/chemokine multiplex analysis, flow cytometry, histology, gene‐expression analysis, microcomputed tomography, and biomechanical analysis. We observed increased early systemic and local inflammatory responses, as well as a significantly higher number of T cells infiltrating the fracture callus. Later in the healing process, we found impaired endochondral ossification in the absence of the GR, leading to persistent cartilage in the calli of the GR gtROSACreERT2 mice, decreased bending stiffness, and a significantly lower proportion of healed bones. Collectively, our data show that the absence of the GR significantly impairs fracture healing associated with a defective cartilage‐to‐bone transition, underscoring an important role of GCs during fracture healing.— Rapp, A. E., Hachemi, Y., Kemmler, J., Koenen, M., Tuckermann, J., Ignatius, A. Induced global deletion of glucocorticoid receptor impairs fracture healing. FASEB J. 32, 2235–2245 (2018). www.fasebj.org